IMPACT OF TRIBULUS TERRESTRIS ON TESTICULAR MORPHOLOGY AND MORPHOFUNCTIONAL STATUS OF THE TESTES - Tilavov Tolibjon Bakhtiyor ugli (Web of Journals Publishing, 2025)
Tribulus terrestris, a plant widely recognized for its potential use in traditional medicine, has gained attention for its influence on male reproductive health. This literature review explores the effects of Tribulus terrestris on the morphological and morphofunctional state of the testes. Studies have demonstrated its role in enhancing spermatogenesis, increasing testosterone levels, and influencing the structural integrity of testicular tissue. The plant's bioactive compounds, particularly saponins, are thought to be responsible for its beneficial effects on male fertility. This review synthesizes findings from various experimental and clinical studies, examining the mechanisms by which Tribulus terrestris affects the testes and male reproductive function. The results suggest that Tribulus terrestris may have therapeutic potential for male infertility and related disorders, though further research is necessary to fully understand its efficacy and safety.
Keywords: Tribulus terrestris, testes, morphology, morphofunctional state, male reproduction, testosterone, spermatogenesis, fertility, plant-based medicine, saponins.